Quantitative evaluation of essential amino acids and omega-3 long-chain polyunsaturated fatty acids from global marine bivalve aquaculture - Karsoon Tan; Peng Xu; Leiheng Huang; Cong Luo; KhaiHang Choong; Zexin Li; Yu Guo; Kit-Leong Cheong (Food Chemistry: X)
The rapid growth of the human population and urbanization has significantly increased the demand for animal proteins. However, expanding protein production from land-based farming, fisheries, and fish aquaculture faces challenges such as limited land and water resources, high carbon emissions, overfished stocks, and reliance on unsustainable fish meal and fish oil. Although many studies highlight bivalve aquaculture as a potential source of sustainable and high-quality proteins, there is limited quantitative data on the production of omega-3 long-chain polyunsaturated fatty acids (n-3 LC-PUFA) and essential amino acid (EAA) from global bivalve aquaculture. In this context, the present study aims to evaluate the current status of n-3 LC-PUFA and EAA production in global bivalve mariculture. The results of this study revealed that bivalves are a valuable source of high-quality animal protein, rich in essential amino acids (EAAs) and n-3 long-chain polyunsaturated fatty acids (LC-PUFA), such as EPA and DHA. Between 2018 and 2022, bivalve production increased by 7.1 % in wet weight, while the growth in crude protein, PUFA, EPA + DHA, and EEA yields was 4.4 %, 5.9 %, 6.5 %, and 3.1 %, respectively. Current production levels of EPA + DHA and EAAs from bivalve aquaculture are sufficient to meet the dietary needs of 78.68 million and 17.3 million healthy adults, respectively. Among different bivalve species, clams and scallops are the most efficient producers of EPA + DHA and EAAs, while oysters produce the least. This study provides a comprehensive overview of lipid and protein production in bivalve aquaculture and offers insights for future management strategies to support the industry's growth.